Potensi Learning Loss terhadap Kemampuan Gerak Dasar pada Siswa Sekolah Dasar Selama Pembelajaran Pendidikan Jasmani di Masa Pandemi - Budi Setyawan, Feri; Puspitarini, Diyah (Universitas Nusantara PGRI Kediri, 2022)
The current Covid-19 pandemic has resulted in new challenges for the people and the Indonesian government, especially in the education sector. One of the affected is physical education, and it is feared that there is learning loss. It is a situation where students lose knowledge and skills due to certain conditions, decreasing their mastery of competencies. This study aims to examine the impact of the Covid-19 pandemic on the potential for learning loss in basic movement skills in elementary school students during Physical Education Learning during the Pandemic Period. The method used in the study is descriptive qualitative, using secondary data taken from various sources. With the gap in learning outcomes due to learning loss, it is necessary to have a mapping to determine the basic motion skills with the highest risk. This study's results show that elementary school physical education learning has the highest risk of learning loss due to distance learning during the Covid-19 pandemic. It is hoped that physical education teachers can respond to this situation by paying more attention to students who have a high learning loss situation, namely by supporting infrastructure in the implementation of distance learning evenly to their students so that there are no gaps in learning outcomes, especially basic movements.